Impact of ROS-Induced Damage of TCA Cycle Enzymes on Metabolism and Virulence of Salmonella enterica serovar Typhimurium - Noster, Janina; Persicke, Marcus; Chao, Tzu-Chiao; Krone, Lena; Heppner, Bianca; Hensel, Michael; Hansmeier, Nicole (Frontiers in Microbiology, 2019)
Salmonella enterica serovar Typhimurium (STM) is exposed to reactive oxygen species (ROS) originating from aerobic respiration, antibiotic treatment, and the oxidative burst occurring inside the Salmonella-containing vacuole (SCV) within host cells. ROS damage cellular compounds, thereby impairing bacterial viability and inducing cell death. Proteins containing Fe-S clusters are particularly sensitive and become non-functional upon oxidation. Comprising five enzymes with iron-sulfur (Fe-S) clusters, the TCA cycle is a pathway most sensitive towards ROS. To test the impact of ROS-mediated metabolic perturbations on bacterial physiology, we analyzed the proteomic and metabolic profile of STM deficient in both cytosolic superoxide dismutases (ΔsodAB). Incapable of detoxifying superoxide anions (SOA), endogenously generated SOA accumulate during growth. ΔsodAB showed reduced abundance of aconitases, leading to a metabolic profile similar to that of an aconitase-deficient strain (ΔacnAB). Furthermore, ewe determined a decreased expression of acnA in STM ΔsodAB. While intracellular proliferation in RAW264.7 macrophages and survival of methyl viologen treatment were not reduced for STM ΔacnAB, proteomic profiling revealed enhanced stress response. We conclude that ROS-mediated reduced expression and damage of aconitase does not impair bacterial viability or virulence, but might even increase ROS amounts in STM, which reinforces the bactericidal effects of antibiotic treatment and immune responses of the host.the host.